Esitutkimus kasvuyrittäjyyden ja kasvuyrityspolitiikan kansantaloudellisesta merkityksestä - Mika Pajarinen; Petri Rouvinen (The Research Institute of the Finnish Economy (ETLA), 2009)
If entrepreneurs are understood to be individuals who perceive new opportunities, introduce them in the market place, and make decisions regarding the organization of production, they may be considered to be the primary source of a society's economic wellbeing. If such entrepreneurship is lacking, an economy is necessarily regressive. Measuring such entrepreneurship, which may also be intrapreneurship within existing organizations and among wage-earners, is challenging; practical applications capture only some facets of a broader phenomenon. Particularly expanding enterprises have a considerable direct economic impact. They also have an indirect impact on the establishment of new and the discontinuation of old establishments as well as on market shares of continuing establishments. Also failed growth entrepreneurs and their companies may have lasting economic impacts. This preliminary study considers the economic role of growth entrepreneurs have in principle as well as considers their empirical role and characteristics in Finland by employing an established OECD definition. It is found that some five per cent of Finnish companies may be considered growth firms; their share was on the rise prior to the financial crisis.
Keywords: 330; Entrepreneurship-Ansatz; Wirtschaftswachstum; Finnland